CASING DESIGN OF THE KY SLIM HOLE WELL IN “X” GEOTHERMAL FIELD - Kelvin Yong; Kris Pudyastuti; Rizki Akbar (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2021)
Geothermal exploration activities including exploration drilling are important stages in a geothermal project. The high uncertainty of the amount of reserves and costs incurred in geothermal projects is a reason for investors to be reluctant to invest at this stage. One alternative is to use slim hole drilling technology instead of using standard hole or big hole technology. Slim hole drilling technology has long been applied in Indonesia in 1993 but has not continued its application. In 2015, slim hole drilling technology began to be used again at the Ijen geothermal field, East Java. Therefore, it is necessary to review the slim hole drilling, especially the casing design and hoisting rig capacity. The purpose of this study is to design a casing for slim hole KY well drilling, namely determining the casing seat at each depth, calculating the thermal stress value which is considered in calculating burst, collapse, and tension pressures. In addition to the casing design, rig sizing calculations were carried out, especially hoisting rig capacity in field X using slim hole reflection well data in the Ijen area, East Java. The results obtained are the determination of the minimum casing setting depth for the production liner 1500 m grade L-80, production casing 680 m, grade L-80, surface casing 240 m grade K-55, and conductor casing 30 m grade K-55. the results of thermal stress analysis, the maximum temperature obtained in the production casing is 425.3ºF and the production liner is 426.67ºF.